2016
DOI: 10.1016/j.bpj.2016.05.050
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cholesterol in Driving IAPP-Membrane Interactions

Abstract: Our knowledge of the molecular events underlying type 2 diabetes mellitus-a protein conformational disease characterized by the aggregation of islet amyloid polypeptide (IAPP) in pancreatic β cells-is limited. However, amyloid-mediated membrane damage is known to play a key role in IAPP cytotoxicity, and therefore the effects of lipid composition on modulating IAPP-membrane interactions have been the focus of intense research. In particular, membrane cholesterol content varies with aging and consequently with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 97 publications
2
78
0
1
Order By: Relevance
“…But in this case a modest acceleration was observed. Comparison of the data presented here with this study and with previous work 51, 52, 59 highlights the high sensitivity of IAPP membrane interactions to lipid composition. In the absence of POPS, addition of 20 mole percent cholesterol to zwitterionic LUVs increased the value of T 50 by 1.5-fold relative to the value in the absence of cholesterol.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…But in this case a modest acceleration was observed. Comparison of the data presented here with this study and with previous work 51, 52, 59 highlights the high sensitivity of IAPP membrane interactions to lipid composition. In the absence of POPS, addition of 20 mole percent cholesterol to zwitterionic LUVs increased the value of T 50 by 1.5-fold relative to the value in the absence of cholesterol.…”
Section: Resultssupporting
confidence: 83%
“…The β-cell membrane contains cholesterol, gangliosides, sphingomyelins, and the level of anionic phospholipids is reported to range from 2.5 to 13.2 mole percent of the total phospholipids 57 . The vast majority of model systems typically contain a much higher percentage of anionic lipids and lack cholesterol and gangliosides, although the effects of cholesterol have been examined in a subset of systems 52, 5759 . Cholesterol is an important component of membranes; it modulates their biophysical properties and is important for the uptake of hIAPP in vivo 58, 60 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that in the presence of model membranes, the α-helical transient intermediates were observed in the early stage of membrane-hIAPP interaction [11]. Intermediate oligomers can disrupt membrane integrity and permeability, lead to ionic homeostasis and signal disturbance, and thereby cause cell death [4,6,1214]. Earlier electron paramagnetic resonance (EPR) spectroscopy and nuclear magnetic resonance (NMR) studies showed that a membrane-bound hIAPP monomer adopts pH- and membrane composition-dependent helical structure in one (residues 9–22) or two regions (residues 7–17 and 21–28) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…10). Studies have shown that the presence of anionic lipids enhance the binding affinity [86], negative curvature strain inducing PE lipids enhanced membrane fragmentation [96], and cholesterol to modulate the membrane mediated aggregation of human-IAPP [97]. The presence of calcium ions has been shown to promote human-IAPP aggregation and membrane fragmentation via a carpet-like mechanism [94].…”
Section: Protein Aggregation and Amyloid Formation In A Membrane Envimentioning
confidence: 99%